Citizens and experts in the public sphere: From technocratic politics to participatory deliberation - Fischer, Frank (1995)
"In the area of political theory and social ethics, the author examines the relationship between citizen and expert in public sphere in the democratic context of participative research. In his analytical discussion, he raises interesting questions from ethical and intellectual perspectives which present an interesting as well as formidable agenda for future research. Finding answers to these, according to him, will have great impact on policy decision-making and also contribute to revitalising at civil society"
Keywords: Political philosophy - India; Political philosophy